2003
DOI: 10.1021/jm025619l
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Statine-Based Cell-Permeable Peptidomimetic Inhibitors of Human β-Secretase

Abstract: We describe the development of statine-based peptidomimetic inhibitors of human beta-secretase (BACE). The conversion of the peptide inhibitor 1 into cell-permeable peptidomimetic inhibitors of BACE was achieved through an iterative strategy of conceptually subdividing 1 into three regions: an N-terminal portion, a central statine-containing core, and a C-terminus. Replacement of the amino acid residues of 1 with moieties with less peptidic character was done with retention of BACE enzyme inhibitory activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(77 citation statements)
references
References 12 publications
1
76
0
Order By: Relevance
“…In addition, APP processing seems to be involved in synaptic function, with endogenous Aß participating in a feedback control of neuronal activity [49]. Therefore, in spite of already existing statin-based peptidomimetic inhibitors of ß-secretase [50,51], the modulation of endogenous Aß under the control of secretases should be foreseen with some caution with regard to possible known and unknown side effects. Our study shows that the level of BACE protein expression is not necessarily linked to Aß formation but is increased in activated astrocytes from AD brains.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, APP processing seems to be involved in synaptic function, with endogenous Aß participating in a feedback control of neuronal activity [49]. Therefore, in spite of already existing statin-based peptidomimetic inhibitors of ß-secretase [50,51], the modulation of endogenous Aß under the control of secretases should be foreseen with some caution with regard to possible known and unknown side effects. Our study shows that the level of BACE protein expression is not necessarily linked to Aß formation but is increased in activated astrocytes from AD brains.…”
Section: Discussionmentioning
confidence: 99%
“…For the C-terminus, L22 sits in a largely hydrophobic pocket with some charge on the periphery. Peptides with largely hydrophobic substitutions at L22 (beta-cyclohexylalanine (15), (19)) tended to bind well, but only the beta-cyclohexylalanine (15) substitution peptide (20) and L-methionine sulfone (22)) in an attempt to interact with charged groups on the periphery of the pocket was not successful and weakened or eliminated binding.…”
Section: Acs Medicinal Chemistry Lettersmentioning
confidence: 99%
“…Inhibitors derived from peptides have been developed for other targets of potential therapeutic importance such as IAPs, 18 beta secretase, 19 14−3−3 proteins, 20 the Bcl family of proteins, 21 and IL-17A. 22 With this in mind, and based on a careful analysis of the structure of the bound substrate peptide, 2 we have designed a potent peptide-based inhibitor of SETD8, which will be useful not only as an in vitro tool to further study SETD8 function but also can potentially be turned into a potent cell-penetrant inhibitor for in vivo studies of SETD8 inhibition.…”
mentioning
confidence: 99%
“…Further, recent reports (Cai et al, 2001;Luo et al, 2001;Roberds et al, 2001) demonstrated that β-secretase knockout mice lack brain Aβ without observed side-effects. In addition, it has been demonstrated in vitro that selective inhibition of β-secretase by a synthetic compound suppresses Aβ secretion in human embryonic kidney cells (Hom et al, 2003).…”
mentioning
confidence: 99%